The ethics of group psychotherapy : principles and practical strategies - Brabender, Virginia; MacNair-Semands, Rebecca (New York, NY : Routledge, 2022)
"The Ethics of Group Psychotherapy provides group psychotherapists with the ethical and legal foundation needed to engage in effective decision-making in their everyday group practices. This text provides readers with a framework for understanding ethical dilemmas through a review of major models of ethical thinking, including principlism, feminism and the ethics of care, and virtue ethics. The authors use this foundation to explore those problems emerging most routinely in group practice, among which are safeguarding members' personal information, protecting members' autonomy, and helping members to process differences-particularly those related to privilege and oppression-in a way that furthers interpersonal relations and social justice. Throughout the text, practical tools such as using assessments to aid in member selection and tracking progress and outcome through Measurement Based Care are offered that bolster the group psychotherapist's effectiveness in ethical decision-making. Featuring questions for discussion and items to assess the reader's mastery of the material, training group psychotherapists will find this text to be a valuable tool in classroom and small-group learning"--
Keywords: Group psychotherapy -- Moral and ethical aspects; Group psychotherapists; PSYCHOLOGY / Psychotherapy / Group; MEDICAL / Ethics